Social Media and the Digital Structural Transformation of the Public Sphere - Philipp Staab; Thorsten Thiel (Theory, Culture & Society, 2022)
This article explores the question of how to understand social media following the Habermasian theory of the structural transformation of the public sphere. We argue for a return to political-economic fundamentals as the basis for analysing the public sphere and seek to establish a characteristic connection between digital-behavioural control and singularised audiences in the context of proprietary markets. In the digital constellation, it is less a matter of immobilising the citizen as a consumer but rather of their political activation – albeit in conditions under which commercial interests have primacy: privatisation without privatism.
Keywords: 320; digital capitalism; Jürgen Habermas; public sphere; social media; structural transformation